FSLC Learning Model: Affect the Ability to Problem-Solving Mathematics in terms of Self-Confidence - Husen, Nisrina; Yunian Putra, Rizki Wahyu; Fadila, Abi (J-PiMat : Jurnal Pendidikan Matematika, 2024)
This study aims to determine the effect of Formulate Share Listen Create learning model on students mathematical problem-solving ability, the effect of self-confidence on students mathematical problem-solving ability, as well as the interaction between Formulate Share Listen Create learning model and self-confidence on students mathematical problem-solving ability. The study employed a quasi-experimental research design with the target population being students in class XI Accounting at SMK Negeri 1 Pekalongan, East Lampung. The sample selection was carried out using a total sampling technique with 32 students from class XI Accounting 1 into the experimental group and 31 students from class XI Accounting 2 assigned to the control group. Tests were used in the findings of this research gathering process and questionnaires, while data analysis was conducted through prerequisite tests and two-way ANOVA hypothesis testing. The study's conclusions showed that the Formulate Share Listen Create learning model has a significant impact on students mathematical problem-solving ability, as does self-confidence. However, no significant interaction was observed between the Formulate Share Listen Create learning model and self-confidence in relation to students mathematical problem-solving ability.  Keyword: Formulate Share Listen Create (FSLC), Problem Solving Mathematics, Self-Confidence